(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2022)
This study aims to improve students’ abilities and describe students’ activities in analyzing the intrinsic elements of novels through cooperative learning with STAD techniques. The subjects involved in this study are class XI IPS 4 SMA Negeri Kebakkramat, Karanganyar. This research method is qualitative with Classroom Action Research (CAR) design. The research procedure includes: the preparation stage, the implementation stage of each cycle, and the final stage. Sources of data in this study are researcher and 36 students of class XI. The research techniques and instruments used are observation, test and questionnaires. The data are collected through observation and questionnaires which then analyzed descriptively, while the data on test results analyzed by using descriptive statistics. The results showed that there was an increase on students’ ability to analyze the intrinsic elements of the novel, marked by an increase in the average score of student skill competencies, from 78.25 (cycle I) to 87.50 (cycle II). Meanwhile, students’ activities in learning in cycles 1 and 2 were good. In cycle 1, out of 15 observed aspects, 7 aspects were observed to be good, 6 aspects were observed to be adequate, and 2 aspects were observed to be lacking. In cycle 2, of the 15 observed aspects, 11 aspects were observed to be Good, and 4 aspects were observed to be Enough.